Adipose Tissue-Derived Extracellular Vesicles Loaded with miR-141-3p Regulate Obesity-Induced Insulin Resistance by Targeting Glycogen Synthesis and Gluconeogenesis - Wang Z; Ma T; Bai G; Fang Q; Ou B; Chen M; Xu P; Tian M; Xu A; Ma Y (International Journal of Nanomedicine)
Zixian Wang,1,2,* Tianyu Ma,3,* Ge Bai,2 Qianchen Fang,2 Biqian Ou,2 Meng Chen,2 Pei Xu,2 Meng Tian,2 Anding Xu,1 Yi Ma1,2 1The First Affiliated Hospital, Jinan University, Guangzhou, Guangdong, 510630, People’s Republic of China; 2Department of Cellular Biology, Institute of Biomedicine, National Engineering Research Center of Genetic Medicine, Key Laboratory of Bioengineering Medicine of Guangdong Province, Jinan University, Guangzhou, Guangdong, 510632, People’s Republic of China; 3School of Medicine, Jinan University, Guangzhou, Guangdong, 510632, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Ma, The First Affiliated Hospital, Jinan University, Guangzhou, Guangdong, 510630, People’s Republic of China, Email tmayi@jnu.edu.cn; Anding Xu, The First Affiliated Hospital, Jinan University, Guangzhou, Guangdong, 510630, People’s Republic of China, Email tlil@jnu.edu.cnPurpose: Insulin resistance, a hallmark feature of type 2 diabetes and cardiovascular diseases, is critically influenced by liver-adipose tissue crosstalk, offering a novel therapeutic strategy for its management. Emerging evidence indicates that extracellular vesicles (EVs) secreted from adipose tissue serve as essential carriers of miRNA-mediated interorgan communication. This study aimed to investigate the regulatory effects of adipose tissue-derived EVs on obesity-induced hepatic insulin resistance and to elucidate the underlying molecular mechanisms by which EV-mediated signaling contributes to metabolic dysfunction.Methods: EVs with miR-141-3p knockout or overexpression were constructed and administered to both in vitro cell models and in vivo mouse models to investigate the regulatory role and underlying mechanisms of miR-141-3p-mediated adipose tissue-derived EVs in obesity-induced hepatic insulin resistance.Results: miR-141-3p is significantly upregulated in adipose tissue-derived EVs from high-fat diet (HFD)-fed mice, as well as in other obesity-related conditions. Furthermore, the knockdown of miR-141-3p in EVs from chow diet (CD-EVs) counteracted the effect in improving obesity-induced hepatic insulin resistance, whereas the overexpression of miR-141-3p in HFD-EVs improved hepatic insulin resistance. Mechanistically, EVs-derived miR-141-3p directly targets PTEN to promote PI3K/AKT signaling, thereby mediating hepatic glucose homeostasis through the regulation of hepatic gluconeogenesis and glycogen synthesis.Conclusion: In summary, our results highlight the emerging role of miR-141-3p in mediating adipose tissue-derived EVs to alleviate obesity-induced hepatic insulin resistance, providing potential therapeutic targets for type 2 diabetes.Keywords: insulin resistance, glycogen synthesis, gluconeogenesis, extracellular vesicles, miRNA, PTEN